Robustness analysis of linear time-varying systems with application to aerospace systems - Biertümpfel, Felix (2021)
In recent years significant effort was put into developing analytical worst-case analysis tools to supplement the Verification & Validation (V&V) process of complex industrial applications under perturbation. Progress has been made for parameter varying systems via a systematic extension of the bounded real lemma (BRL) for nominal linear parameter varying (LPV) systems to IQCs. However, finite horizon linear time-varying (LTV) systems gathered little attention. This is surprising given the number of nonlinear engineering problems whose linearized dynamics are time-varying along predefined finite trajectories. This applies to everything from space launchers to paper processing machines, whose inertia changes rapidly as the material is unwound. Fast and reliable analytical tools should greatly benefit the V&V processes for these applications, which currently rely heavily on computationally expensive simulation-based analysis methods of full nonlinear models.